Design, Synthesis, and Antitumor Activity of Erlotinib Derivatives - Mao, Long-fei; Wang, Zhen-Zhen; Wu, Qiong; Chen, Xiaojie; Yang, Jian-Xue; Wang, Xin; Li, Yue-Ming (Frontiers in Pharmacology, 2022)
Nineteen erlotinib derivatives bearing 1,2,3-triazole moiety were designed, synthesized and evaluated for their potential against different cancer cell lines. The structures of the synthesized compounds were confirmed by 1H NMR, 13C NMR and HR MS. Preliminary antitumor activity assay results indicated that some compounds showed remarkable inhibitory activity against different cancer cell lines including the corresponding drug-resistant ones. Among these compounds, 3d was the most potent one with IC50 of 7.17±0.73μM (KYSE70TR), 7.91±0.61μM(KYSE410TR), 10.02±0.75μM (KYSE450TR), 5.76±0.33μM (H1650TR)and 2.38±0.17μM (HCC827GR).Preliminary mechanism study suggested that these erlotinib-1,2,3-triazole derivatives suppress cancer cells proliferation through EGFR-TK pathway.